2004
DOI: 10.1038/sj.ijo.0802798
|View full text |Cite
|
Sign up to set email alerts
|

Micro-environmental and socio-demographic determinants of childhood obesity

Abstract: AIM:To review the available data in Spain about the socio-demographic and home environmental determinants in children and adolescents. METHOD: Review of the main studies conducted in Spain that have analysed the relationship between overweight and socioeconomic and environmental determinants in children and adolescents. RESULTS: In children aged 6-7 y from Aragó n (Spain), the socio-demographic determinants of childhood overweight were size of municipality, year of examination, gender, and province; in adolesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
22
0
10

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 31 publications
10
22
0
10
Order By: Relevance
“…A grande preocupação é que essa transição já vem ocorrendo na faixa etária pediátrica, com prevalências de sobrepeso semelhantes àquelas encontradas nos países desenvolvidos, como Inglaterra 25 , Estados Unidos 3 e Canadá 26 . No entanto, nestes países, o excesso de peso vem atingindo gradativa e mais freqüentemente o indivíduo de menor poder aquisitivo, onde o aspecto financeiro deixa de ter tanta importância, passando a ser considerados de maior risco os indiví-duos com baixo acesso à educação [27][28][29][30][31] . Neste estudo, os resultados apresentados revelaram diferença altamente significante entre a prevalência de excesso de peso de escolas públicas e privadas, com maiores percentuais para as últimas, demonstrando um padrão típico e ainda vigente em países em desenvolvimento [27][28][29][30][31][32] .…”
Section: Discussionunclassified
“…A grande preocupação é que essa transição já vem ocorrendo na faixa etária pediátrica, com prevalências de sobrepeso semelhantes àquelas encontradas nos países desenvolvidos, como Inglaterra 25 , Estados Unidos 3 e Canadá 26 . No entanto, nestes países, o excesso de peso vem atingindo gradativa e mais freqüentemente o indivíduo de menor poder aquisitivo, onde o aspecto financeiro deixa de ter tanta importância, passando a ser considerados de maior risco os indiví-duos com baixo acesso à educação [27][28][29][30][31] . Neste estudo, os resultados apresentados revelaram diferença altamente significante entre a prevalência de excesso de peso de escolas públicas e privadas, com maiores percentuais para as últimas, demonstrando um padrão típico e ainda vigente em países em desenvolvimento [27][28][29][30][31][32] .…”
Section: Discussionunclassified
“…In the analyzed sample of the AVENA study, including immunological data, females showed a prevalence of 17% of overweight and 4% of obesity; the figures for males were 22 and 8%, respectively. Detailed information of overweight and obesity prevalence within the complete AVENA study is described elsewhere in this supplement by Moreno et al 14 Characteristics of the two groups are shown in Table 1. There were no age differences between groups; however, as expected, we found significantly higher BMI and sum of skinfolds, reflecting more adipose tissue in the overweight/ obesity groups.…”
Section: Resultsmentioning
confidence: 99%
“…Adolescence is a crucial period in life and implies multiple physiological and psychological changes that affect nutritional needs and habits 7,8 . Existing research indicates that risk factors for noncommunicable diseases have to be placed in an ecological context, which needs a collaborative strategy within the multiple sectors that impact on the diseases 9 . Inadequate dietary habits and physical inactivity are the major preventable risk factors for the occurrence of non-communicable diseases 10 .…”
mentioning
confidence: 99%